IMPLEMENTASI APLIKASI SOFTWARE NATURAL NETWORK MENDETEKSI TINGKATAN SERANGAN DDOS PADA JARINGAN KOMPUTER - Etza nofarita (Elkom : Jurnal Elektronika dan Komputer, 2021)
Security issues of a system are factors that need to be considered in the operation of information systems, which are intended to prevent threats to the system and detect and correct any damage to the system. Distributed Denial of Services (DDOS) is a form of attack carried out by someone, individuals or groups to damage data that can be attacked through a server or malware in the form of packages that damage the network system used. Security is a mandatory thing in a network to avoid damage to the data system or loss of data from bad people or heckers. Packages sent in the form of malware that attacks, causing bandwidth hit continuously. Network security is a factor that must be maintained and considered in an information system. Ddos forms are Ping of Death, flooding, Remote controled attack, UDP flood, and Smurf Attack. The goal is to use DDOS to protect or prevent system threats and improve damaged systems. Computer network security is very important in maintaining the security of data in the form of small data or large data used by the user.